Memorial to the Right Honourable Neville Chamberlain, M.P., Minister of Health (1925)
1925 1925 1920s 2 pages Private and Confidential. MEMORIAL TO The Right Honourable NEVILLE CHAMBERLAIN, M.P., Minister of Health. Sir, WE, the undersigned Members of the House of Lords, the House of Commons, Medical, Scientific, Health, and Philanthropic Societies, and Workers' Organisations respectfully beg of you to consider the advisability of activating Local Authorities, acquainted with the requirements of their respective Districts, to prepare and circulate popular Food Leaflets which, without advocating any special system of diet, would spread information about healthy, nourishing, economical foods, and, without urging its exclusive use, would direct attention to the value of finely ground whole wheat meal Bread. These leaflets could, with little expense, be distributed by Health Visitors, at Schools for Mothers, etc. A Demand for wholesome, nourishing Bread could thus be created all over the country which could soon be supplied by Local Millers and Bakers, and the health of the rising generation would thus be greatly promoted. We beg to remind you that during the last four years Resolutions and Memorials have been sent to the Ministry of Health urging the publication of Educational Food Leaflets by Municipal Authorities, by Members of Parliament, representing all parties, by over one hundred and fifty Members of Medical and Scientific Associations, and by Health, Temperance, Labour and Philanthropic Societies. THE PRESENT DISTRESS AND UNEMPLOYMENT MAKE THE SPEEDY DISSEMINATION OF PLAIN PRACTICAL INFORMATION ABOUT HEALTHY, NOURISHING ECONOMICAL FOODS A MATTER OF NATIONAL IMPORTANCE. We therefore beg respectfully to urge you to ask Municipal Authorities to devote their attention to this subject. Name & Titles Address Date 292/840/1/18